Semiologi, Strukturalisme, Post-Strukturalisme, dan Kajian Desain Komunikasi Visual? - Adiwijaya, Dominique Rio (Bina Nusantara University, 2011)
Some concepts from theoretical schools such as semiology, structuralism and post-structuralism are referenced in today’s discussions of design. Its language-ladeness which makes it appeals initially as pertinent to visual communication. Yet under the alleged reason of cross-disciplinary, design study often just wants to pick up one or two concepts without sufficient willingness to grasp their primer. It is very much contradictory since sheer picking up is an anti-intellectual attitude, whereas all forms of study are intellectual in character. Great scholar Alfred North Whitehead once complained those who quoted him in bits and pieces, as did not understand what is meant by his theory. It is true that design has a cross-disciplinary character. But since design is neither philosophy nor social science, it demands a study of their primer with respect (not oversimplifying), within the spirit of liberal arts. Hence this article does not intend to give 'structuralist' account of design; instead it is a brief study into primer of semiology, structuralism and post-structuralism. Its significance for design would be reflected afterwards.